2007
DOI: 10.1002/pits.20226
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive study of school discipline referrals in first grade

Abstract: School discipline referrals (SDRs) may be useful in the early detection and monitoring of disruptive behavior problems to inform prevention efforts in the school setting, yet little is known about the nature and validity of SDRs in the early grades. For this descriptive study, SDR data were collected on a sample of first grade students who were at risk for developing disruptive behavior problems (n = 186) and a universal sample (n = 531) from 20 schools. Most SDRs were given for physical aggression and the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 38 publications
0
18
0
2
Order By: Relevance
“…The reporting of Black females' discipline sanctions in the literature seems to serve as a means to further highlight the inequitable discipline experiences of Black males rather than to demonstrate how disproportionate discipline practices might also negatively impact the school experiences of Black girls. The lack of emphasis on the discipline experiences of Black girls may in part be due to the perception that girls in general pose less risk for behavior problems given their greater academic achievement and to gendered racial bias, in favor of Black boys, in discipline referrals and sanctions (Gregory 1995;Myhill and Jones 2006;Olser 2006;Rusby et al 2007;Skiba et al 2002). However, Black males' greater risk for receiving exclusionary discipline practices does not preclude Black females from experiencing inequitable discipline practices.…”
Section: Introductionmentioning
confidence: 94%
“…The reporting of Black females' discipline sanctions in the literature seems to serve as a means to further highlight the inequitable discipline experiences of Black males rather than to demonstrate how disproportionate discipline practices might also negatively impact the school experiences of Black girls. The lack of emphasis on the discipline experiences of Black girls may in part be due to the perception that girls in general pose less risk for behavior problems given their greater academic achievement and to gendered racial bias, in favor of Black boys, in discipline referrals and sanctions (Gregory 1995;Myhill and Jones 2006;Olser 2006;Rusby et al 2007;Skiba et al 2002). However, Black males' greater risk for receiving exclusionary discipline practices does not preclude Black females from experiencing inequitable discipline practices.…”
Section: Introductionmentioning
confidence: 94%
“…For instance, Tobin and Sugai (1999) found that office discipline referral (ODRs) and suspensions received in 6th grade predicted later chronic discipline problems, such as violent behavior and school failure. Rusby et al (2007) found that ODRs in kindergarten served as a significant predictor of problem behavior in 1st grade and that ODRs in 1st grade predicted parent-and teacher-reported problem behavior at the end of the school year. Also, several studies have further supported the validity of school discipline records as an ecologically important measure of externalizing problem behavior in school settings because they are relatively stable across elementary, middle, and high schools (Irvin et al 2004;McIntosh et al 2008;McIntosh et al 2006;McIntosh et al 2010;March and Horner 2002;Nelson et al 2002;Tobin and Sugai 1999).…”
Section: Introductionmentioning
confidence: 95%
“…Policies of this kind are generally not considered in discussions about early childhood. However, there has been evidence of increased discipline referrals in the early grades (Rusby et al, 2007) and a corresponding increase in the diagnosis of attention deficit hyperactivity disorder (ADHD) (Loughran, 2003). For affected families, discipline policies can have a significant impact on parents' interactions with schools.…”
Section: The Rationale For Partnershipmentioning
confidence: 99%